(untitled) (Al-Qamar, 2022)
The study is carried out to uncloak the life of transsexuals who face discontentment in a Pakistani society. The study highlights that in the third world countries, such issues are in dominance. The problem is especially prevalent in Sub-Saharan African and South Asian countries. The research is qualitative in nature because it provides textual analysis of the novella A Prince Who Destroyed My Life. The research seeks to examine the status, the repercussions, various programs and recommendations on the lives of transsexuals through a literature review. The repercussions of transsexuals are highlighted in this piece, with the girls at risk of early pregnancies with life-threatening complications along with her transsexual baby. Each country should set its own mid and long-term targets to manage their lives significantly. The afore-mentioned problem has been a long-standing one in the society. Leading clerics, well versed in matter of religion, should be asked to speak out on the problem and ensure that people are fully informed about the issue in a country or a state where violation of transsexual is still common, especially in village areas and less developed parts of the country.